Pengaruh Kualitas Layanan dan Fitur Produk BSI Mobile terhadap Kepuasan Nasabah Bank Syariah Indonesia KCP Veteran Makassar - Masykur, Nur Ahlamiah Tri Putri; Fathurrahman, Fathurrahman; Muslihati, Muslihati (Asian Journal of Islamic Studies and Da'wah, 2024)
This research aims to determine the influence of service quality and BSI mobile product features on customer satisfaction at Bank Syariah Indonesia KCP Veteran Makassar. The sample in this research is customers who use BSI mobile at Bank Syariah Indonesia KCP Veteran Makassar. The method used in this research is a quantitative method with a survey method that uses a questionnaire as a data collection instrument. Based on the research results, it was found that the first hypothesis was accepted, namely that service quality has a positive and significant impact on customer satisfaction in using BSI mobile. Likewise with the second hypothesis, where product features have a positive and significant impact on customer satisfaction in using BSI mobile. And with that, the third hypothesis is also accepted, which shows that together or simultaneously service quality and product features have a positive and significant impact on customer satisfaction at Bank Syariah Indonesia KCP Veteran Makassar.